2018
DOI: 10.1029/2017jc013691
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Inputs to Chinese Marginal Seas: Impact of Industrialization and Development of China

Abstract: In the past decades, China has experienced substantial economic growth and industrialization. However, the effects of vast development of China on Hg input to the nearby oceans are still unclear. In this study, the influx and isotopic compositions of Hg in four 210Pb‐dated sediment cores were examined to investigate changes in Hg deposition to the marginal seas off China over a century. Nearshore cores had higher Hg influxes than offshore cores. Increases of Hg influxes started since the 1950s, which coincides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 82 publications
3
23
1
Order By: Relevance
“…It needs to be noted that both concentrations and influxes of THg exhibited a slight decrease from 2001 to 2010, especially for industrial Hg and atmospheric Hg, while differently, the influxes of riverine Hg kept increasing (Figures 5 and 6). This seems a bit different from other published studies which reported an increasing trend in industrial Hg inputs and a decreasing trend in riverine Hg inputs (Yin et al, 2018). Actually, the observed change indicated by only one data point here may not represent a trend, and maybe it was just a fluctuation induced by uncertainties (e.g., sampling contingency).…”
Section: Core-3contrasting
confidence: 97%
See 3 more Smart Citations
“…It needs to be noted that both concentrations and influxes of THg exhibited a slight decrease from 2001 to 2010, especially for industrial Hg and atmospheric Hg, while differently, the influxes of riverine Hg kept increasing (Figures 5 and 6). This seems a bit different from other published studies which reported an increasing trend in industrial Hg inputs and a decreasing trend in riverine Hg inputs (Yin et al, 2018). Actually, the observed change indicated by only one data point here may not represent a trend, and maybe it was just a fluctuation induced by uncertainties (e.g., sampling contingency).…”
Section: Core-3contrasting
confidence: 97%
“…As summarized in the box plot (Figure ), the Δ 200 Hg and Δ 204 Hg signatures in Yellow Sea central core‐3 (in this study) were similar to those in Yellow Sea surface sediments (Meng et al., 2019), Yellow Sea central core (Yin et al., 2018) and gaseous Hg 0 (Fu et al., 2018), rather than East China Sea nearshore core‐1 and offshore core‐2 (in this study), East China Sea surface sediments (Meng et al., 2019), East China Sea nearshore core (Yin et al., 2018), particulate‐bound Hg (Fu et al., 2019), and wet precipitation Hg (Huang et al., 2018). These suggest that part of Hg in sediments from the central mud area of Yellow Sea was likely originally traced back to atmospheric Hg 0 .…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The aim of the present study is to investigate potential sources of Hg in Mediterranean deep-sea and Adriatic sediments. To our knowledge only a few studies report stable isotope compositions of Hg in deep-sea sediments and most of them were conducted close to estuaries or coastal region 1518 . Ogrinc et al .…”
Section: Introductionmentioning
confidence: 99%